Analisis Kesalahan dalam Pemecahan Masalah Logaritma Kelas X MIPA SMA Harapan Jaya - Cipto Hardiansyah; Bitman Manullang; Santri Chintia Purba (Brillo Journal, 2022)
This study aims to find out the various errors of students in working on logarithmic problems so that the specific objectives in this study are: (1) Knowing the types of errors made by students in solving logarithmic problems. (2) Knowing the factors that cause student errors in solving logarithmic problems. This research was conducted at Harapan Jaya High School. Based on this goal, the results of this study can be used by teachers to overcome the same problem in the future. The approach used in this study is a qualitative approach. The research method used is a case study. The samples used in this study were 3 students of class X MIPA SMA Harapan Jaya with purposive sampling technique. The results of this study indicate that: (1) There are 3 types of errors made by students, namely conceptual errors, procedural errors and arithmetical errors. (2) The factors that cause student errors are the condition of students being tired, learning conditions that are not supportive and not focused and not thorough. Based on the results of this study, teachers are expected to be able to assist students in minimizing existing errors by implementing various learning models that increase students' accuracy in solving various problems. In addition, teachers can also provide feedback to students so that students can find out their mistakes and help students overcome any errors that exist.